Riders of the Purple Sage - Grey, Zane, 1872-1939 (Salt Lake City, UT : Project Gutenberg, 1998)
"Riders of the Purple Sage" by Zane Grey is a Western novel published in 1912. Set in 1871 Utah, the story follows three characters$1 (BBern Venters, Jane Withersteen, and gunfighter Jim Lassiter$1 (Bas they face persecution from local Mormon leaders in the fictional town of Cottonwoods. Jane, a wealthy Mormon rancher, resists pressure to enter a polygamous marriage while befriending outsiders. The novel features cattle-rustling, kidnapping, and gunfights across Southern Utah's dramatic canyon country. Called "the most popular western novel of all time," it helped define the Western genre. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Riders_of_the_Purple_Sage
Release date is 1998-05-01
Bill Brewer, Rick Fane and David Widger
Keywords: Western stories; Utah -- Fiction; Women ranchers -- Fiction; Latter Day Saint women -- Fiction; Polygamy -- Fiction